EGCG inactivates a pore-forming toxin by promoting its oligomerization and decreasing its solvent-exposed hydrophobicity. (1st February 2023) - Gabriel, Justus M.; Tan, Thomas; Rinauro, Dillon J.; Hsu, Claire M.; Buettner, Caleb J.; Gilmer, Marshall; Kaur, Amrita; McKenzie, Tristan L.; Park, Martin; Cohen, Sophie; Errico, Silvia; Wright, Aidan K.; et al.
Abstract: Natural proteinaceous pore-forming agents can bind and permeabilize cell membranes, leading to ion dyshomeostasis and cell death. In the search for antidotes that can protect cells from peptide toxins, we discovered that the polyphenol epigallocatechin gallate (EGCG) interacts directly with melittin from honeybee venom, resulting in the elimination of its binding to the cell membrane and toxicity by markedly lowering the extent of its solvent-exposed hydrophobicity and promoting its oligomerization into larger species. These physicochemical parameters have also been shown to play a key role in the binding to cells of misfolded protein oligomers in a host of neurodegenerative diseases, where oligomer-membrane binding and associated toxicity have been shown to correlate negatively with oligomer size and positively with solvent-exposed hydrophobicity. For melittin, which is not an amyloid-forming protein and has a very distinct mechanism of toxicity compared to misfolded oligomers, we find that the size-hydrophobicity-toxicity relationship also rationalizes the pharmacological attenuation of melittin toxicity by EGCG. These results highlight the importance of the physicochemical properties of pore forming agents in mediating their interactions with cell membranes and suggest a possible therapeutic approach based on compounds with a similar mechanism of action as EGCG. Highlights: The pore-forming toxin melittin perturbs cell membranes, resulting in cell death. Epigallocatechin gallate (EGCG) targets the physicochemical properties of melittin. EGCG lowers the solvent-exposed hydrophobicity of melittin. EGCG promotes the oligomerization of melittin. These changes attenuate melittin binding to cell membranes and cytotoxicity.